Efforts to Improve Learning Outcomes in the Game of Volleyball Through Modification of Learning Tools and Media - Nurshafa, Dina Aliyah; Lengkana, Anggi Setia; Saptani, Entan (Indonesian Journal of Sport Management, 2024)
This research aims to determine the improvement in learning outcomes in the game of volleyball by modifying learning tools and media for class V SDN Gunung Sari. The type of research used is classroom action research (PTK). The research subjects were fifth-grade students at SDN Gunung Sarı, totalling 23 students. The data collection techniques used are observation, tests, and documentation. Data analysis techniques include quantitative and qualitative descriptive analysis. The research results found that using modified learning tools and media can improve learning outcomes in volleyball for class V students at SDN Gunung Sari. The analysis results significantly improved from pre-cycle, cycle I, cycle II, and cycle III. The results of learning the volleyball game in the pre-cycle in the complete category were 39% or nine students. The results of learning the volleyball game in cycle I in the whole category were 65% or 15 students. The results of learning the game of volleyball in cycle II in the complete category were 82% or 19 students, and in cycle III in the whole category, it was 100% or 23 students. This research concludes that the application of modified learning tools and learning media in volleyball games can improve learning outcomes for class V students at SDN Gunung Sari.